Pengaruh Komisaris Independen, Komite Audit, Leverage, Dan Sales Growth Terhadap Tax Avoidance Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi - Christin Maria Febryanti; Erna Sulistyowati (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Manufacturing companies in the consumer goods industry sector consumer non-cyclical was chosen in this study as a research subject because of the sector company consumer non-cyclical produce and distribute goods and services that support daily needs so that they have economic stability and future potential and are not affected by adverse economic conditions. The purpose of this study was to determine the influence of independent commissioners, audit committees, leverage, and sales growth to tax avoidance on the company consumer non-cyclical registered on the IDX for 2017 – 2021. The sampling technique was carried out by purposive sampling and data collection techniques using secondary data documentation techniques in the form of financial reports. The data analysis technique uses multiple linear regression analysis. Data processing in this study uses SPSS. The results of the study show that the independent commissioners have an effect on tax avoidance. The audit committee has no effect on tax avoidance. Leverage no effect on tax avoidance. Sales Growth no effect on tax avoidance. Keywords: independent commissioners, audit comittee, leverage, sales growth, tax avoidance.